Transformasi Digital TVRI Sulawesi Selatan Manfaatkan Fitur Siaran Langsung Platform Media Sosial - SITTI WAHYUNI ARTINI (DIII Prodi Humas Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2022)
Television of the Republic of Indonesia, South Sulawesi, carried out a digital transformation by utilizing social media platforms for live broadcasts. Utilization of social media platforms to respond to media transformation in TVRI. This research was conducted with the aim of answering research questions, namely (1) Why does TVRI South Sulawesi utilize the live broadcast feature of social media platforms? and (2) How does South Sulawesi TVRI take advantage of the live broadcast feature of social media platforms? This study involved 4 informants who are leaders and employees of TVRI South Sulawesi. The results of the study found that TVRI South Sulawesi utilized the live broadcast feature on 3 social media platforms, namely Facebook, YouTube, and Instagram. This innovation was carried out as an effort to strengthen the distribution reach of news produced by TVRI South Sulawesi. As evidenced by the live broadcast feature of social media platforms, it can make it easier for the public to access information in real time as long as they are connected to the internet.